PENGARUH VARIASI LUBANG KATALIS TERHADAP EMISI GAS BUANG SEPEDA MOTOR BERBAHAN BAKAR CAMPURAN PERTALITE DAN ETANOL - M. Rizal Triwahyu Z; Wawan Trisnadi Putra; Kuntang Winangun (Universitas Muhammadiyah Ponorogo, 2021)
From the development and progress of a country, increasing the speed of growth, and increasing speed, from that we need a word to reduce exhaust emissions produced by motors because the catalyst is made of copper and it is easy for us to get the basic materials and for the manufacture of the catalyst is also a little easy. Its utilization is to reduce HC and CO gases from incomplete combustion of motorized vehicles and fuel mixed with ethanol which slightly helps to increase the combustion of motor vehicles. Seen from the CO results from the use of full hole catalyst, it is 2.7490, in the right hole is 2.4650 and the left hole is 2.6290. seen the results of HC from the use of the full hole of 597.30, on the right hole of 492.60 and the left hole of 637.70.